Analyzing the impact of team-building interventions on team cohesion in sports teams: a meta-analysis study - Kwon, S. H. (Frontiers in Psychology, 2024)
Introduction: Participation in team sports requires collaboration among multiple individuals over an extended period. Success in the game relies on more than just individual excellence; it necessitates effective teamwork. Team-building interventions have been shown to enhance team functioning, particularly in fostering cohesion among sports teams. This study aims to identify crucial factors in team-building interventions that contribute to improved team cohesion in sports teams.